Wygasanie oboczności leksykalnych stryj ║ stryk oraz wuj ║ uj w dobie średniopolskiej - Michalska-Górecka, Paulina (Slavia Occidentalis, 2019)
The aim of this article is to show the rivalry of the two pairs of variants: stryj ║ stryk and wuj ║ uj in the history of the Polish language, especially with respect to Middle Polish. Samples of these forms were taken from dictionaries which note historical Polish lexis – from Old Polish to the 20th century. Moreover, the article is an attempt at identifying the era in which this rivalry finished and which forms developed as norms in the literary language.